2013
DOI: 10.1002/ejlt.201300012
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic production of modified 2‐dodecyl‐sophorosides (biosurfactants) and their characterization

Abstract: Alkyl sophorosides, a special type of sophorolipids, can be produced using Candida bombicola cultures with glucose as main carbon source and 2-dodecanol as co-substrate. The dominating component, 2-dodecylsophoroside SL-E 2-12 , was purified via medium pressure liquid chromatography (MPLC) and used as substrate for further enzymatic modifications. Using b-glucuronidase in aqueous media the first modification gave a glycosidic cleavage of the acetyl glucose unit leading to 2-dodecyl-glucoside GL-A 2-12 . In a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The modification of 2-dodecyl sophorolipid 99, prepared by fermentation with 2-dodecanol as substrate, was performed by Recke et al (Scheme 15). 56 The 2-dodecyl sophorolipid 99 was transformed into the 2-dodecyl glucolipid 100 via the selective removal of a glucose unit with the β-glucuronidase enzyme. Subsequently, this glucolipid was acylated at the 6′-position with sebacic acid towards glucolipid 101.…”
Section: Modifications Towards New Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of 2-dodecyl sophorolipid 99, prepared by fermentation with 2-dodecanol as substrate, was performed by Recke et al (Scheme 15). 56 The 2-dodecyl sophorolipid 99 was transformed into the 2-dodecyl glucolipid 100 via the selective removal of a glucose unit with the β-glucuronidase enzyme. Subsequently, this glucolipid was acylated at the 6′-position with sebacic acid towards glucolipid 101.…”
Section: Modifications Towards New Derivativesmentioning
confidence: 99%
“…These hydroxyalkyl-etherified sophorolipid esters were incorporated in cosmetic compositions to prepare powdered compressed cosmetic materials such as face powder, cheek rouge, highlight or eye shadow or stick-shaped cosmetic materials such as stick- Scheme 15 Acylations at the 6'-and 6''-position of sophorolipid 99 and glucolipid 100. 56 shaped rouge, lip cream, stick-shaped eye shadow or cosmetic pencil. 61 They were also applied in cosmetics as moistureretaining and moisturizing agents, giving a less sticky and better moisturizing feeling than conventional moisturizers such as glycerine, sorbitol and ethylene glycol.…”
Section: Non-selective Reactions At the Sugar Headmentioning
confidence: 99%
“…Sophorolipids are very promising biosurfactants and have been object to several studies aiming to modify and to improve their properties. Recke et al (2013) recently reported the enzymatic modification of alkyl sophorolipids, a special sophorolipid produced by Candida bombicola , resulting in the formation of a new and unexplored glycolipids . These glycolipids have been acylated with fatty acids originating from other glycolipids, namely 3‐hydroxydecanoic acid from rhamnolipids and 17‐hydroxyoctadecanoic acid obtained from sophorolipids employing Novozyme 435 in toluene.…”
Section: Enzymatic Modification Of Microbial Glycolipidsmentioning
confidence: 99%
“…Being odor‐ and tasteless and non‐irritant, they might furthermore be very interesting for applications as emulsifier in food or cosmetic formulations . Additionally, antimicrobial , antiviral and antifungal properties of glycolipids, as well as their possible application as anti‐tumor agent are described in literature. This versatility and the physico‐chemical properties of glycolipids thus might allow their use in many different applications, e.g., in cleaning products or in food and pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The infl uence of the purifi ed glycolipids on the surface tension (σ) of aqueous solutions and on the interfacial tension (γ) of water/n-hexadecane systems was determined at 25 °C with a tensiomat (TE1C MGW; Lauda, Lauda-Königshofen, Germany) using the ring method (Recke et al, 2013).…”
Section: Determination Of Physicochemical Propertiesmentioning
confidence: 99%